The implications of trade liberalization for diet and health: a case study from Central America - Hawkes Corinna; Thow Anne Marie (BMC, 2009)
Abstract Background Central America has undergone extensive trade liberalization over the past two decades, and has recently signed a Free Trade Agreement with the United States. The region is also experiencing a dual burden of malnutrition with the growth of dietary patterns associated with the global 'nutrition transition'. This study describes the relationship between trade liberalization policies and food imports and availability, and draws implications for diet and health, using Central America as a case study region. Methods Changes in tariff and non-tariff barriers for each country were documented, and compared with time-series graphs of import, production and availability data to show the outcome of changes in trade policy in relation to food imports and food availability. Results Changes in trade policy in Central America have directly affected food imports and availability via three avenues. First, the lowering of trade barriers has promoted availability by facilitating higher imports of a wide range of foods. Second, trade liberalization has affected food availability through promoting domestic meat production. Third, reductions in barriers to investment appear to be critical in expansion of processed food markets. This suggests that changes in trade policies have facilitated rising availability and consumption of meat, dairy products, processed foods and temperate (imported fruits) in Central America. Conclusion This study indicates that the policies of trade liberalization in Central American countries over the past two decades, particularly in relation to the United States, have implications for health in the region. Specifically, they have been a factor in facilitating the "nutrition transition", which is associated with rising rates of obesity and chronic diseases such as cardiovascular disease and cancer. Given the significant cost of chronic disease for the health care system, individuals and the wider community, it is critical that preventive health measures address such upstream determinants of poor nutrition.